Tunneled dialysis catheter utilization and patency: a retrospective-prospective study from a tertiary care hospital in Karachi Pakistan - Tahir, Misbah; Ali, Muhammad; Siddiqui, Danial Khalid; Durrani, Noureen; Iqbal, Jawaid; Mustafa, Khalid (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the patency of tunnel dialysis catheters and their results in patients in a tertiary care setting. Method: The retrospective-prospective, observational study was conducted at the Department of Interventional Radiology, Liaquat National Hospital, Karachi, from September 2021 to February 2022, and comprised records of patients who underwent tunnel dialysis catheters placement from July 2019 to December 2020. Data regarding age, gender, residence, comorbidity, catheter placement site, use of antibiotics before catheter insertion, reasons for catheter removal, and total catheter days was retrieved from the medical record. Data was analysed using STATA 14. Results: Of the 134 patients, 74(56.9%) were males and 56(43.1) were females. The overall median age was 65 years (interquartile range: 56.75-70.25 years). Catheters were electively removed in 97(72.4%) patients, while in 19(14.2%), 16(11.9%) and 2(1.5%) cases, catheters were removed due to infections, blockage and physical damage, respectively. Mortality due to catheter-related complications was not found. Incidence per 10,000 catheter days of overall infection, bacteraemia and other infections during one year was 8.4, 5.3 and 3.1, respectively. Overall infection-free survival rate was seen for 19 patients (survival rate=67.6%). Survival rate from catheter removal was seen in 36 patients (survival rate=53.2%). Conclusion: When all precautions were followed to circumvent catheter-related issues, tunnel dialysis catheters were found to be a viable option for haemodialysis until permanent access for dialysis is gained or a kidney transplant is performed. Key Words: Tunnel dialysis catheter, End-stage kidney disease, Chronic kidney disease, Interventional radiology.